An Architecture Model for a Distributed Virtualization System - Pessolani, Pablo Andrés (2019)
Virtualization technologies are massively adopted to cover those requirements in which Operating Systems (OS) have shown weakness, such as fault and security isolation. They also add features like resource partitioning, server consolidation, legacy application support, management tools, among others, which are attractive to Cloud service providers. Hardware virtualization, paravirtualization, and OS-level virtualization are the most widely used technologies to carry out these tasks, although each of them presents different levels of server consolidation, performance, scalability, high-availability, and isolation. The term “Virtual Machine” (VM) is used in issues related to hardware virtualization and paravirtualization technologies to describe an isolated execution environment for an OS and its applications. Containers, Jails, Zones are the names used in OS-level virtualization to describe the environments for applications confinement. Regardless of the definition of the virtualization abstraction, its computing power and resource usage are limited to the physical machine where it runs. The proposed virtualization architecture model breaks this issue, distributing processes, services, and resources to provide distributed virtual environments based on OS factoring and OS containers. The outcome is a Distributed Virtualization System (DVS) which allows running several distributed Virtual Operating System (VOS) on the same cluster. A DVS also fits the requirements for delivering high-performance cloud services with provider-class features as high-availability, replication, elasticity, load balancing, resource management, and process migration. Furthermore, a DVS is able to run several instances of different guest VOS concurrently, allocating a subset of nodes for each instance (resource aggregation), and to share nodes between them (resource partitioning). Each VOS runs isolated within a Distributed Container (DC), which could span multiple nodes of the DVS cluster. The proposed architecture model keeps the appreciated features of current virtualization technologies, such as confinement, consolidation and security, and the benefits of DOS, such as transparency, greater performance, high-availability, elasticity, and scalability.